Peran Pemerintah Desa Dalam Pengembangan UMKM Di Desa Sibalaya Selatan - Aziza Rusda; Andi Herman Jaya; Harnida W. Adda (International Forum of Researchers and Lecturers, 2023)
Sibalaya Selatan Village has 6 SMEs consisting of culinary SMEs, selling/product SMEs and service SMEs. South Sibalaya Village does not yet have policies or programs related to the development of MSMEs in South Sibalaya Village. In the development of MSMEs, there is a need for cooperation between internal parties, namely business actors and external parties, namely the government to optimize their potential and improve the economy. This is what prompted research on the role of the village government in the development of MSMEs in South Sibalaya Village.